Control interno y su incidencia en las cuentas por cobrar de la empresa fundación para el desarrollo integral espoir, cantón Quevedo, período 2012. - Rosero Jalca, Janine Alexandra (2014)
This research project aims to investigate the issue: Internal Control and its Impact on Accounts Receivable Business Development Foundation for Integral Espoir, Canton Quevedo, 2012 period and for this we had to select a service company dedicated to providing loans to the general public, is an entity specialized in microcredit Cooperation housing emerging, individually and education, which enjoys the confidence of national and international organizations, therefore the objectives of this study are to analyze processes Accounts Receivable Foundation, evaluate the system in Credit Control, to review the Accounts Receivable Overdue loans and Evaluation Report on Internal Control, in order to verify the results achieved in this research project…..